Convection-permitting climate simulations using SINGV-RCM and WRF over the Maritime Continent - Venkatraman Prasanna; Srivatsan V. Raghavan; Anurag Dipankar; Jianyu Liu; Gerald Lim; Aurel Moise; Nguyen Ngoc Son; Bhenjamin Jordan Lozada Ona; Pavan Harika Raavi; Anupam Kumar; Jianjun Yu; Chen Chen; et al. (Climate Dynamics, 2026)

Evaluating SINGV ‐ RCM for Long‐Term High‐Resolution Climate Simulations Over Southeast Asia - Venkatraman Prasanna; Anurag Dipankar; Jianyu Liu; Gerald Lim; Aurel Moise; Xin Rong Chua; Chen Chen; Jian Jun Yu; Pavan Harika Raavi; Fei Luo; Muhammad Eeqmal Hassim; Sandeep Sahany; et al. (International Journal of Climatology, 2025)
Long‐term convection‐permitting dynamical downscaling has been carried out over Southeast Asia and the Western Maritime Continent, using the Singapore Regional Climate Model (SINGV‐RCM) at 8 and 2 km spatial resolutions, respectively. SINGV‐RCM is forced with ERA5 reanalysis data for 36 years (1979–2014) at 8 km resolution over Southeast Asia (79E‐160E; 16S‐24N) with a regular update of the sea surface temperature at 6‐h intervals. Subsequently, the 8 km domain simulation is used for forcing a smaller domain over the Western Maritime Continent at a resolution of 2 km (93E‐110E; 7.2S‐9.9N) for 20 years (1995–2014). Rainfall characteristics including the diurnal cycle, monthly annual cycle, and daily extremes over land and ocean from the two simulations are evaluated against the high‐resolution IMERG precipitation data available from 2001 to 2014. SINGV‐RCM captures mean and extreme rainfall well; however, there are noticeable biases in the rainfall magnitude over the Ocean. These biases agree with the earlier publications on convection‐permitting simulation over the maritime Continent. Models' skill is further evaluated in terms of mean, bias, pattern correlation and RMSE for 8 and 2 km simulations against the IMERG precipitation data.

High-resolution dynamically downscaled projections of future extreme temperatures, heatwaves and exposure in Southeast Asia - Jianjun Yu; Aurel F. Moise; Sandeep Sahany; Venkatraman Prasanna; Xin Rong Chua; Chen Chen; Muhammad E.E. Hassim; Gerald Lim; Fei Luo; Anupam Kumar; Puyang Liu; Pavan Harika Raavi (Science of The Total Environment, 2025)

SINGV-RCM: the convection-permitting regional climate model for Singapore - Venkatraman Prasanna; Anurag Dipankar; Jianyu Liu; Gerald Lim; Aurel Moise; Xin Rong Chua; Claudio Sanchez; Chen Chen; Jianjun Yu; Harika Pavan Raavi; Fei Luo; Muhammad Eeqmal Hassim; et al. (Climate Dynamics, 2024)
The development of the Singapore regional climate model (SINGV-RCM) is documented in this study. The model’s skill in predicting mean and extreme rainfall over the Maritime Continent at 8 km and 2 km grid resolution is assessed using observed rainfall. The model’s sensitivity to vertical grid and convection parametrization is also evaluated. Results demonstrate the added value of downscaling to 8 and 2 km. The spatial and temporal characteristic of the diurnal rainfall is shown to be in good agreement with the observation. The model also demonstrates skill in capturing extreme rainfall. In general, the rainfall in the 8 km and 2 km simulations are quite similar, when regrided to a coarser resolution. Even then, the convection-permitting simulation at 2 km is found to add value over the 8 km simulation, particularly in capturing the higher rainfall thresholds. Mean biases over the ocean is found to be larger than that over the land, which suggests the need to further tune SINGV-RCM for long climate simulations.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Cytoskeletal regulation by Dictyostelium Ras subfamily proteins - Chinten James Lim; George B. Spiegelman; Gerald Weeks (Journal of Muscle Research and Cell Motility, 2002)